DECISION MAKING UNDER THE CONDITIONS OF RISK AND UNCERTAINTY IN SOME ENTERPRISES OF PRISHTINA AND FERIZAJ - Dervishi, Aferdita; Kadriu, Ibish (European Scientific Journal, ESJ, 2014)
Managers take decisions in all levels but they are often faced with uncertainty and risk. In the field of management it is not done much to study the attitude of managers behave in relation to their decision they take in risk circumstances. The purpose of this paper is to reflect decision taking as one of very important managerial concepts, with attention to conditions of uncertainty analyse on some private and public enterprises of country. The aim of this paper is to identify criteria, types and process of decision taking under conditions of uncertainty and risk in organisations that is in reality reflection of respective image of organisation. It is used normative method using primary and secondary data. The qualitative research is based in the sample of 20 managers of enterprises in two municipalities of Kosovo. As a technique for collection of primary data is used direct interview with managers. Based on the findings is ascertained that assessment of risk and uncertainty on decision taking is made mainly based on intuition. Such decisions are made without taking sufficient information, without precise analyse and without going through 8 steps of decision taking. It is also not paid needed importance to experts of respective fields while IT tools were not used to analyse the risk.